Keeping Quiet: Factors that Hinder Anger Expression at Work - Stickney, Lisa T.; Geddes, Deanna (International Association of Conflict Management 24th Annual Conference Proceedings, 2011)
More research is emerging that finds workplace anger expression (versus suppression) is more likely to promote positive individual and organizational outcomes. However, many angry employees at work choose to remain silent rather than express their anger. What factors contribute most to this decision? Using content and factor analysis, we identify three key categories of factors that hinder anger expression at work, most to least frequent, respectively: professional courtesy, fear of repercussions, and organizational norms. We argue that rather than self-focused concerns of retaliation or sanctioning, most people fail to speak up when angry because of perceptions that “professionals” do not express anger, or the concern that anger expression shows a lack of respect for fellow organizational members. Although this is admirable in its other-oriented (versus self-centered) focus, there is a false assumption that keeping one’s anger and concerns hidden about a problematic workplace situation is helpful for the organization. Management can play a key role in changing social norms to allow for honest and helpful expressions of anger by employees without fear of appearing unprofessional or receiving organizational sanctions.
Keywords: anger at work; anger expressions; expressed anger; workplace anger